Teologi Mu’tazilah Dan Pengaruhnya Di Bidang Sosial, Politik, dan Ekonomi - Rizka Maulida; M Fandriansyah (AL-MUFASSIR, 2022)
This study discusses the influence of the Mu'tazilah on Islamic civilization when the Mu'tazilah emerged. The Islamic Caliphate at that time experienced disputes and wars. Some of the Abbasid caliphs made progress in the socio-political and economic fields. Under these conditions the Mu'tazilah became the madhhab that was held, of course the official Mu'tazilah theology had an influence either directly or indirectly. This study is qualitative in nature and uses historical descriptive research methods. The results of this study are that the Mu'tazilah have an important role in Islamic civilization in the development of the economic, social, and political fields.